Cost Varying Interval Transportation Problem under Two Vehicle - Arpita Panda; Chandan Bikash Dasb (Journal of New Results in Science)
–In this paper we represent a two-vehicle cost varying interval transportation model (TVCVITM). To determine thecost interval of cost parameters of interval transportation problem(ITP) we use two vehicle cost varying TP. In this model thetransportation cost varies due to capacity of vehicles as well asamount of transport quantity. At first we propose an algorithmto determine limits of the interval of unit transportation cost. Thisis an uncertain multi-level programming model. Then formulatecorresponding multi-objective crisp model. To solve this, applyfuzzy programming technique. A numerical example is presentedto illustrate the TVCVITM